2013
DOI: 10.1103/physrevlett.110.246101
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Subsurface Ordering of Oxygen Vacancies on the ReducedCeO2(111)Surface Using Density-Functional and Statistical Calculations

Abstract: Oxygen vacancies on ceria (CeO(2)) surfaces play a crucial role in catalytic applications, yet whether vacancies are at surface or subsurface sites on reduced CeO(2)(111), and whether vacancies agglomerate or repel each other, is still under discussion, with few and inconsistent experimental results. By combining density-functional theory (DFT) in the DFT+U (U is an effective onsite Coulomb interaction parameter) approach and statistical thermodynamics, we show that the energetically most stable near-surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 33 publications
15
103
0
Order By: Relevance
“…On the (111) surface, methanol desorption and its transformation to formaldehyde are competing processes, but the weak interaction between methanol and the surface results in a large peak in the TPD at low temperatures. Still, some methanol molecules survive on the surface long enough to react, possibly pinned by undersurface vacancies [62,63]. This is clearly evidenced in the TPD experiments where the low temperature peak (methanol desorption) is larger than the others for the (111) surface under stoichiometric conditions.…”
Section: Discussionsupporting
confidence: 49%
“…On the (111) surface, methanol desorption and its transformation to formaldehyde are competing processes, but the weak interaction between methanol and the surface results in a large peak in the TPD at low temperatures. Still, some methanol molecules survive on the surface long enough to react, possibly pinned by undersurface vacancies [62,63]. This is clearly evidenced in the TPD experiments where the low temperature peak (methanol desorption) is larger than the others for the (111) surface under stoichiometric conditions.…”
Section: Discussionsupporting
confidence: 49%
“…7 A seminal experimental study 8 proposed that O vacancies cluster together. Notwithstanding one theoretical study supporting this 9 , other experimental [10][11][12] and theoretical 6,13,14 works suggest that lattice relaxation effects cause vacancies to repel each other, with the prior experimental evidence for vacancy clustering being attributed to fluorine contamination of the ceria crystal 12 . Connected with the formation of O vacancies is the localization of the extra electrons.…”
Section: Introductionmentioning
confidence: 76%
“…on the Ce f electrons with U = 5 eV, consistent with prior work. 5 As with prior work 5,14,16,17 , we restrict ourselves to ferromagnetic states for the Ce 3+ f electrons. Single and double vacancy calculations were performed using 3x3 supercells, and a few double vacancy calculations using 4x4 supercells were carried out to test the impact of vacancy density on vacancy formation energies (herein all vacancy formation energies are normalized by the number of vacancies).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Murgida et al used DFT+U with a U value of 4.5 eV for Ce and the PBE exchange and correlation functional employing VASP to address the crucial question of whether vacancies agglomerate or repel each other. 16 They showed that the energetically most stable near-surface oxygen vacancy structures for a broad range of vacancy concentrations have all vacancies at subsurface oxygen sites. In another interesting study, Zhang et al investigated the adsorption of an Au atom on O-vacancy sites and proposed that O-vacancies and O-vacancy clusters could also be anchoring sites for Au nucleation.…”
mentioning
confidence: 99%